Phenolate and phenylthiolate ligand complexes containing Zn(II), Ni(II) and Cu(II) - Cowling, Frances Natalie (2017)
Chapter 1 provides an introduction to metalloenzymes and discusses Ni-containing superoxide dismutase (NiSOD), which features Ni-thiolate ligation at the active site, and Cu containing galactose oxidase, which utilises phenoxyl radicals to perform its catalytic function. Studies concerning low molecular weight analogue complexes of each active site are reviewed and their relevance with respect to enzyme structure and function is discussed. Chapter 1 concludes with a description of the aims of this thesis project. Chapter 2 discusses of the preparation of a series of Zn(II), Ni(II) and Cu(II) Schiff-base diphenolate complexes incorporating the four novel pentadentate pro-ligands, [H2tBuLOH], [H2tBuLOCl], [H2tBuLOtBu] and [H2tBuLOOMe]. The different pKa values of the para-substituted arylamines (H, Cl, tBu and OMe) appear to modulate the electrochemical properties and redox behaviour of the Zn(II), Ni(II) and Cu(II) diphenolate complexes. Cyclic voltammetric, spectroelectrochemical and EPR spectroscopic studies reveal the first oxidation processes of [Zn(tBuLOOMe)]and[Cu(tBuLOOMe)]are associated with ligand-based oxidation processes, yielding kinetically inert species possessing phenoxyl radical character. Conversely, the first oxidation process of [Ni(tBuLOOMe)] appears to be metal-based. Chapter 3 discusses of the syntheses of Schiff-base diphenolate and dithiolate complexes with a diamine bridge that incorporate pendant heterocyclic groups, with the potential to coordinate in an axial position to a metal centre that possess equatorial N2O2 or N2S2 coordination environments. We targeted the syntheses and characterisations of these complexes as analogues of the active site of NiSOD.Initial attempts to synthesise a diamine incorporating a pendant imidazole donor followed previously established synthetic approaches. The use of protecting groups to protect the NH group of the imidazole ring was unsuccessful. The syntheses of Ni(II) Schiff-base diphenolate and dithiolate complexes was attempted by using the pro-ligands, [H2tBuLOOH]and [H2tBuLSOH]and a post complexation step that involved a reaction of the OHpendant of the Schiff-base ligand with an aromatic or heterocyclic functionalised acid chloride. Functionalisations of the [Ni(tBuLOOH)]and [Ni(tBuLSOH)]to incorporatependant imidazole (Imid), pyridyl (PyN), furan (Fu) and pyrrole (Pyr) yielded crude products and attempts to purify these products proved unsuccessful.[Ni(tBuLOPh)]could be isolated and X-ray crystallographic studies of [Ni(tBuLOR)] (R = OH and Ph) and [Ni(tBuLSOH)] demonstrate that each centre adopts an approximate square planar geometry. Electrochemical investigations of [Ni(tBuLOR)] (R = OH, Ph)and[Ni(tBuLSOH)] showed that each exhibit irreversible redox processes and demonstrate that the OH and phenyl ester functionalities pendant to the ligand backbone do not stabilize theproducts formed following the oxidation of [Ni(tBuLOR)] (R = OH, Ph)and[Ni(tBuLSOH)]. Chapter 4 extends the research described in Chapter 3 through the synthesis of [Zn(tBuLOOH)] and [Cu(tBuLOOH)] and the attempted functionalisation of the OH group in these complexes to incorporate additionalpendant heterocyclic groups including imidazole(Imid), pyridyl (PyN), furan (Fu) and pyrrole (Pyr) together with phenyl (Ph). X-ray crystallographic studies show that [Cu(tBuLOOH)] possesses an approximately square planar coordination geometry with the metal centre bound by diimine and diphenolate donors.The frozen solution X-band EPR spectra of [Cu(tBuLOR)] (R =Ph, PyN, Fu, Pyr and Imid) are similar to one another and confirm each complex possesses a paramagnetic Cu(II) S = ½ d9 metal centre. The similarity between each EPR spectrum as R is varied suggests that the functional group pendant to the ligand backbonedoes not interact greatly with Cu (II) centre in [Cu(tBuLOR)]. [Zn(tBuLOOH)] was isolated and mass spectrometric data suggested that [Zn(tBuLOR)] (R =Ph, PyN, Fu, Pyr and Imid) had formed, however pure products could not be isolated. Electrochemical studies of [Cu(tBuLOR)] (R = OH, Ph, PyN, Fu, Pyr and Imid) revealtwo irreversible redox processes. [Cu(tBuLOPyN)] possesses first and second redox processes that are ca.0.14 V and 0.23V more positive than their [Cu(tBuLOR)] (R = OH, Ph, Fu, Pyr and Imid) counterparts. This suggests that the pyridyl functionalization of the pendant arm in [Cu(tBuLOPyN)]may stabilize its oxidation product. Chapter 5 provides a conclusion to the thesis and draws together the principal themes of each chapter.